THE BIOGRAPHY AND THE BIOGRAPHED: RELECTIONS ABOUT AFONSO HENRIQUES DE LIMA BARRETO - Luciana da Costa Ferreira (Travessias, 2009)
This text aims to study the profile of Lima Barreto, a writer from Rio de Janeiro. The mean analysis will be about lifes contradictions. Discussing that the biography cant define a